LEGAL MULTILINGUALISM AS A RIGHT TO REMAIN UNILINGUAL – FICTION OR REALITY? - DOCZEKALSKA, Agnieszka (Comparative Legilinguistics, 2016)
The rule of law, guaranteed in democratic countries, requires that those who are subject to the law should be able to know the law (the principle of legal certainty). Hence, a citizen should have an access to laws in a language that he or she knows. Therefore, in multilingual settings, the principle of legal multilingualism requires that legal acts be drafted in all official languages and provides that all language versions be equally authentic and contribute to the meaning of a legal act. Thus, citizens can read laws in a language they understand. On the other hand, since no two languages are identical, the discrepancies between language versions, due to the nature of language or a mistake, are inevitable. The paper identifies methods applied by judges of the Court of Justice of the European Union and national courts to deal with the discrepancies between language versions of EU legal acts. Through case law analysis, the paper demonstrates whether the principle of legal multilingualism actually guarantees legal certainty and what courts can do to make the right to remain unilingual in a multilingual setting real.